Time Varying Neonatal Seizure Localization - Deburchgraeve, W.; Cherian, P. J.; Vos, M. De; Swarte, R. M.; Blok, J. H.; Visser, G. H.; Govaert, P.; Huffel, S. Van (Methods of Information in Medicine, 2010)
Background: A common cause for damage to the neonatal brain is a shortage in the oxygen supply to the brain or asphyxia. Neonatal seizures are the most frequent manifestation of neonatal neurologic disorders. Multichannel EEG recordings allow topographic localization of seizure foci.Objectives: We want to objectively determine the spatial distribution of the seizure on the scalp, the location in time and order the dominant sources in the brain based on their strength.Methods: In this paper we combine a method based on higher order CP-decomposition with subsequent singular value decomposition (SVD).Results: We illustrate the abilities of the method on simulated as well as on real neonatal seizure EEG.Conclusions: The proposed method provides reliable time and spatial information about the seizure, gives a clear overview of what is going on in the EEG and allows easy interpretation.
Keywords: CP-decomposition; neonatal EEG; seizure localization